Perceptions and attitudes of rural Intermediate Phase learners of English as First Additional Language for communicative competence in Limpopo - Maja, Margaret Malewaneng (Journal for Language Teaching, 2024)
This study explored the perceptions and attitudes of rural Intermediate Phase learners of English First Additional Language (EFAL) for communicative competence in Limpopo. The study was grounded in self-determination theory (SDT) using a qualitative approach. Six focus group interviews were used to gather information from thirty learners who were purposely selected from three primary schools. Each group had five learners from grades 5 to 6. Data was analysed using a thematic approach. The study found that most learners viewed English as useful and popular to other languages because it gives them the freedom to express themselves, connects them with people who do not speak their language and affords them the opportunity to become successful pro-fessionals. However, some learners perceived English as a threat to their Sepedi language. This study suggests that teachers should motivate and support learners in engaging in peer mutual learning, by creating social interactive activities that offer learners oppor¬tunities to learn the English language together.